Shallow Water Internal Waves and Associated Acoustic Intensity Fluctuations - Hareesh Kumar, P.V.; Sanilkumar, K.V.; Panchalai, V.N. (Defence Science Journal, 2006)
Physical oceanographic and acoustic data were simultaneously collected from the coastal waters of the Arabian Sea. Acoustic transmissions were carried out from an anchored vessel using 620 Hz transducer and received by an array of hydrophones moored at ~5 km away from the anchorage. Thermal structure in this region was characterised by a tri-layer structure, ie, a strong thermocline (> 0.4 oC/m) sandwiched between an upper (< 10 m) and bottom (> 25 m) homogeneous layer. High-resolution (sampled at 10 s interval) temperature data from moored sensors revealed intense internal wave activity. The maximum value of Brunt-Vaisala frequency, which is the maximum frequency limit of internal waves in the thermocline, suggests that the upper frequency limit of the internal wave, which can be generated during this period, is 23 cph (2.6 min). High and low frequency waves caused variations of ~3 oC and ~5 oC respectively in the temperature field. But the low frequency internal waves were found to contain maximum energy compared to the high frequency waves. Fluctuations of 8-12 dB were noticed in the measured acoustic intensity values in the presence of low frequency internal waves. Simulation studies carried out using parabolic equation model using 620 Hz source indicated well-defined ducted propagation with minimum transmission loss, when the source was kept within the homogeneous layer. The presence of tri-layer thermal structure, ie, a strong gradient layer sandwiched between an upper and bottom homogeneous layer, caused surface and bottom channel propagation in this region.